Pelatihan Pengembangan Biskuit Kimpul di Desa Wedoro Klurak Kecamatan Candi Kabupaten Sidoarjo - Puspitasari, Diana (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2023)
Wedoro Klurak Village, Candi District, Sidoarjo Regensy has a good climate for the development of Micro, Small and Medium Enterprises. This is supported by a large population so that there are amny available workers, the location is close to the city of Surabaya making it easier for marketing. In Wedoro Klurak Village, micro businesses are developing which are engaged in food processing. This growing business utilizes the surrounding community as workers in the production process. In addition, the surrounding community also benefits as a reseller. The products developed so far are limited to types of traditional food with market coverage still limited to the Candi District area. Based on this condition, it is necessary to develop business diversification in the types of products, develop marketing, and improve business management. The purpose of this activity are: transfer of appropriate technology for processing biscuits or kimpul cookies to the public as an alterbative product diversification. Methods of implementing training on community service are: theoretical explanation of processing kimpul biscuits and packaging of food products, and direct practice of processing kimpul biscuits from raw materials to packaging. The results of the implementation of the training showed that the participants were enthusiastic and interested in implementing and developing kimpul processed products. Community interests to the nature of the product which is non-gluten, so it is safe for children with special needs, or people who limit wheat consumption.